Analisis Perbandingan Experiential Value antara Hong Tang dan Black Ball serta Hubungannya dengan Customer Satisfaction - Gunawan, Annetta (Bina Nusantara University, 2014)
Black Ball and Hong Tang are two pioneers of Taiwanese dessert sellers in Jakarta. Both of them have product offering characteristics that are alike and have the same target market. From the initial observation, the researcher found that even though Black Ball has more outlets than Hong Tang, but Black Ball seems to be less popular than Hong Tang. The consumersâ preferences are varied, there are some consumers prefer Hong Tang, but there are also those who choose Black Ball, because of the food quality, the service provided, and also the experiences they get during the consumption process. Therefore, both Black Ball and Hong Tang have to consider about the experiential value to be offered to their customers, in order to increase their customer satisfaction, so that they can sustainably survive in the midst of challenging competition. The objectives of this research are to examine whether there is any difference of experiential value dimensions and customer satisfaction between Hong Tang and Black Ball and to examine the relationship between experiential value dimensions and customer satisfaction of Hong Tang and Black Ball. The result of this research concludes that there is no difference of all experiential value dimensions and customer satisfaction between Hong Tang and Black Ball and there is a strong and significant relationship between all experiential value dimensions and customer satisfaction of Hong Tang and Black Ball.